The Oriented Attachment Model Applied on Crystal Growth of Hydrothermal Derived Magnetite Nanoparticles - Ahmad Fadli; Amun Amri; Iwantono Iwantono; Arisman Adnan; Sunarno Sunarno; Sukoco Sukoco; Mayangsari Mayangsari (Indonesian Journal of Chemistry, 2020)
Magnetite (Fe3O4) nanoparticles are very promising to be applied as a drug delivery system (DDS) for cancer chemotherapy. In this research, the crystal growth of hydrothermal derived magnetite particles was studied by oriented attachment (OA) model. The OA model was used to investigate the mechanism and the statistical kinetic of crystal growth. The crystal diameter change as a function of time with different concentration was measured using XRD. Firstly, 0.3248 g FeCl3 and 1.1764 g of sodium citrate, as well as 0.3604 g urea were dissolved into 40 mL of distilled water in a reactor. Subsequently, the reactor temperature was maintained at 210 °C and reaction time of 3.5–12 h in an air oven. The morphology of obtained particles was characterized using TEM, whereas VSM was used to determine the magnetic hysteresis curve. The XRD pattern showed that magnetite was obtained at temperature 210 °C and 3.5 h reaction time, as well as its intensity increased with reaction time. The crystal size of Fe3O4 was 9.44 nm at 3.5 h and appropriate with the oriented attachment model. The magnetite nanoparticles with shaped core-shell size less than 50 nm and suitable for biomedical application especially as drug delivery.